An unknown input observer based framework for wide-area control of inter-area oscillations with local measurement - Patel, Abhilash; Ghosh, Sandip (Elsevier B.V., 2022)
Inter-area oscillations in power system limit the power transfer capability through tie-lines. For stable operation, wide-area power system stabilizers are deployed to provide sufficient damping. However, as the feedback is through a communication network, it brings challenges such as additional communication layers and cybersecurity issues. To address this, a framework for synthesizing remote signals from local measurement as feedback in the wide-area power system stabilizer is proposed. The remote signal is synthesized using different variants of observers in a case study of a two-area benchmark system. The proposed framework can improve the damping of inter-area oscillations for static output feedback controller. The presented framework should help to design attack-resilient controller design in smart grid.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: observer; power system stability; wide-area controller; Circuit oscillations; Controllers; Electric power system control; Energy transfer; Feedback control; System stability; Area controllers; Inter-area oscillations; Local measurement; Power System Stabilizer; Remote signals; Damping